2001
DOI: 10.1097/00006123-200101000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Susceptibility of Brain Tumors to the Antiangiogenic Effects of an αv Integrin Antagonist

Abstract: The cyclic pentapeptide EMD 121974 may become a treatment option specific to brain tumors. Because of its antiangiogenic effect, its use may be especially indicated after tumors are removed surgically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 39 publications
2
126
0
2
Order By: Relevance
“…The RGD motif of integrins is targeted by a very specific drug EMD121974, designed to block the interaction between avb3 and avb5 integrins on endothelial cells and ECM, thereby interfering with a key process in angiogenesis. On the basis of an in vivo study where significant tumor regression was observed in a xenograft model treated with EMD121974 [181], clinical trials with this compound in combination with radiation therapy are currently being conducted.…”
Section: Anti-invasion Clinical Trialsmentioning
confidence: 99%
“…The RGD motif of integrins is targeted by a very specific drug EMD121974, designed to block the interaction between avb3 and avb5 integrins on endothelial cells and ECM, thereby interfering with a key process in angiogenesis. On the basis of an in vivo study where significant tumor regression was observed in a xenograft model treated with EMD121974 [181], clinical trials with this compound in combination with radiation therapy are currently being conducted.…”
Section: Anti-invasion Clinical Trialsmentioning
confidence: 99%
“…Details of the orthotopic (intracranial) xenotransplant model in nu/ nu mice have been described previously [6]. Recent modifications of this protocol included the injection of only 10 5 U87MG tumor cells in 1 mL RPMI via continuous infusion over 20 min into the forebrain 1.5 mm lateral and 0.5 mm anterior to the bregma, at a depth of 2.5 mm.…”
Section: Orthotopic Brain Tumor Modelmentioning
confidence: 99%
“…EMD 121974, a potent cyclic RGD peptide antagonist of a v -integrins, has been found to detach both brain capillary and brain tumor cells from the matrix proteins vitronectin and tenascin, resulting in significant apoptosis of both cell types [5]. In addition, daily intraperitoneal administration of EMD 121974 inhibited growth of U87MG glioblastoma and DAOY primitive neuroectodermal brain tumor cell lines xenotransplanted into the forebrain of nude mice resulting in increased survival [6]. Only tumors smaller than 1.5 mm at the initiation of therapy responded to the daily systemic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…У этих же животных при ортотопическом росте медуллобластомы или глиобластомы человека продолжительность жизни после имплантации опухолевых клеток составляла не более 4-6 недель, в то время как все животные, получавшие циленгитид, выживали в течение 16 недель наблюдения. Однако при подкожном (гетеротопическом) росте опухолей лечение циленгитидом было не эффективно [32]. По данным другой работы [33], выживаемость крыс с ортотопической локализацией глиобластомы человека, как в контрольных группах, так и леченых циленгитидом, составляла 30 дней после прививки опухоли.…”
Section: пептидомиметикиunclassified